Biochemical profile of benzalkonium chloride toxicity in broiler birds - MANDAL, P K; GUPTA, M K; SINGH, K K; YADAVA, R (The Indian Journal of Animal Sciences, 2014)
The biochemical profile of benzalkonium chloride (Be) toxicity was studied in 12-day-old, broiler birds (80). They were divided into 5 equal groups. BC was given in the drinking water@ 100,300,500 and 700 ppm to groups T1, T2, T3 and T4 respectively. Control, birds (C) were kept on plain water. Estimation was carried out on 10th, 20th, 30th and 40th day of experiment. Results revealed on one hand hypoglycaemia and significantly reduced alkaline phosphatase activity, on the other hand higher values were observed in the level of serum AST, ALT, urea and urie add. There was also hyperkalaemia and hypenatraemia. Total protein and albumin exhibited reduced level up to 20th day of toxicity followed by fall in their level on 30th and 40th day. Significant biochemical alteration as compared to control was recorded mainly in 500 and 700 ppm dose level indicating significant alteration in the normal functional status of the body, on the other hand, no remarkable change was recorded in 100 arid 300 ppm dose level which suggested that at this dose rate systemic involvement is minimal and can not prove to be hazardous for the broiler birds.